«Täglichkeiten von Frieden». Marlene Streeruwitz liest Bertha von Suttner: [«Everyday features of Peace». Marlene Streeruwitz reads Bertha von Suttner] (Studia austriaca, 2025)
In 1889, Bertha von Suttner published her novel Die Waffen nieder! (Down with Weapons!), hailed as one of the most important works of anti-war literature. Suttner shows the brutality and senselessness of war and presents profound arguments against violence and militarism. Marlene Streeruwitz’s essay on Bertha von Suttner, published in 2014, is a highly topical reflection on the Nobel Peace Prize-winner’s text, which is largely forgotten today. The article aims to analyze Suttner’s novel and Streeruwitz’s essay comparatively and to work out a universal contribution of women writers to pacifist thinking and peace policy.